2017
DOI: 10.18632/oncotarget.15841
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of fruits and vegetables and risk of renal cell carcinoma: a meta-analysis of observational studies

Abstract: BackgroundThere have been inconsistent results about the association between consumption of fruits and vegetables and renal cell carcinoma (RCC) risk. We conducted a meta-analysis of the published observational studies to explore this association.ResultsNineteen observational studies (4 cohort, 1 pooled and 14 case-control studies), involving 10,215 subjects with RCC were part of this meta-analysis. The SRR for the highest vs. the lowest intake of vegetables was 0.73 (95% CI: 0.63–0.85; Pheterogeneity = 0.004,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…We identified the following exposures associated with the incidence of RCC: healthy dietary pattern [ 64 ], unhealthy/Western pattern [ 64 ], drinking pattern [ 64 ], fish [ 65 ], total fat [ 87 ], sweetened carbonated beverage [ 66 ], beer [ 67 ], wine [ 67 ], spirits [ 67 ], riboflavin [ 68 ], vitamin B6 [ 68 ], folate [ 68 ], vitamin B12 [ 68 ], saturated fat [ 87 ], methionine [ 68 ], choline [ 68 ], betaine [ 68 ], all meats [ 15 ], tea [ 69 ], fruit fiber [ 70 ], vegetable fiber [ 70 ], cereal fiber [ 70 ], legume fiber [ 70 ], dietary inflammatory index [ 71 ], vitamin C [ 72 ], seafood [ 16 ], animal fat [ 16 ], cholesterol [ 16 ], total protein [ 87 ], animal protein [ 87 ], plant fat [ 16 ], plant protein [ 87 ], sweetened beverages (including artificially sweetened beverages and sugar-sweetened beverages) [ 73 ], polyunsaturated fat [ 87 ], vitamin E [ 74 ], coffee [ 75 ], vitamin D [ 76 ], dietary nitrate [ 77 ], dietary nitrite [ 77 ], glycemic index [ 78 ], glycemic load [ 78 ], monounsaturated fat [ 87 ], dietary fiber [ 78 ], alcohol (light) [ 79 ], alcohol (moderate) [ 79 ], alcohol (heavy) [ 79 ], alcohol (any) [ 79 ], vegetables [ 80 ], fruit [ 80 ], red meat [ 17 ], processed meat [ 17 ], cruciferous vegetables [ 81 ], poultry [ 15 , 16 ], fruit and non-starchy vegetables [ 87 ], non-starchy vegetables [ 87…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified the following exposures associated with the incidence of RCC: healthy dietary pattern [ 64 ], unhealthy/Western pattern [ 64 ], drinking pattern [ 64 ], fish [ 65 ], total fat [ 87 ], sweetened carbonated beverage [ 66 ], beer [ 67 ], wine [ 67 ], spirits [ 67 ], riboflavin [ 68 ], vitamin B6 [ 68 ], folate [ 68 ], vitamin B12 [ 68 ], saturated fat [ 87 ], methionine [ 68 ], choline [ 68 ], betaine [ 68 ], all meats [ 15 ], tea [ 69 ], fruit fiber [ 70 ], vegetable fiber [ 70 ], cereal fiber [ 70 ], legume fiber [ 70 ], dietary inflammatory index [ 71 ], vitamin C [ 72 ], seafood [ 16 ], animal fat [ 16 ], cholesterol [ 16 ], total protein [ 87 ], animal protein [ 87 ], plant fat [ 16 ], plant protein [ 87 ], sweetened beverages (including artificially sweetened beverages and sugar-sweetened beverages) [ 73 ], polyunsaturated fat [ 87 ], vitamin E [ 74 ], coffee [ 75 ], vitamin D [ 76 ], dietary nitrate [ 77 ], dietary nitrite [ 77 ], glycemic index [ 78 ], glycemic load [ 78 ], monounsaturated fat [ 87 ], dietary fiber [ 78 ], alcohol (light) [ 79 ], alcohol (moderate) [ 79 ], alcohol (heavy) [ 79 ], alcohol (any) [ 79 ], vegetables [ 80 ], fruit [ 80 ], red meat [ 17 ], processed meat [ 17 ], cruciferous vegetables [ 81 ], poultry [ 15 , 16 ], fruit and non-starchy vegetables [ 87 ], non-starchy vegetables [ 87…”
Section: Resultsmentioning
confidence: 99%
“…Increasing vegetable consumption was found to be inversely related to RCC risk in our study. A meta-analysis conducted by Zhang et al found that the protective effect of vegetables was diminished after adjustment for body mass index [ 80 ], implying that obesity might be an important intermediate mechanism between vegetable consumption and the incidence of RCC. Obesity has been acknowledged by the guidelines of the European Association of Urology as a risk factor for RCC [ 146 ], which might be related to the inverse association between vegetables and obesity [ 147 – 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of chronic diseases have been studied with regard to FVs consumption, such as type 2 diabetes, [28] depression, [29] cardiovascular disease, [30,31] and cancers. [32,33] While eating more FVs has been showed to reduce the risk of all those disease, its association with gallstone disease still needs more studies.…”
Section: Discussionmentioning
confidence: 99%
“…A high-fiber diet, for instance, has been associated with a lower incidence of RCC, while the high concentration of nitrite, present in processed meat, may increase the risk. [46][47][48][49] A higher incidence of RCC has been documented in women who consume large quantities of red meat and/or processed meat, with a greater increase among those in pre-menopausal period. 50,51 No association was found in the male population, nor in relation to white meat consumption, regardless of gender.…”
Section: Nutritionmentioning
confidence: 99%